2003
DOI: 10.1073/pnas.0431081100
|View full text |Cite
|
Sign up to set email alerts
|

Conducting nanowires built by controlled self-assembly of amyloid fibers and selective metal deposition

Abstract: Recent research in the field of nanometer-scale electronics has focused on the operating principles of small-scale devices and schemes to realize useful circuits. In contrast to established ''topdown'' fabrication techniques, molecular self-assembly is emerging as a ''bottom-up'' approach for fabricating nanostructured materials. Biological macromolecules, especially proteins, provide many valuable properties, but poor physical stability and poor electrical characteristics have prevented their direct use in el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
586
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 704 publications
(599 citation statements)
references
References 47 publications
(67 reference statements)
8
586
0
5
Order By: Relevance
“…32 For recombinant amyloid proteins, gold nanoparticles attached to the protein surface serve as nucleation sites to promote the electroless reduction of silver and gold enabling nanowire growth. Only one metal nanoparticle per 250 amino-acids was needed to create conductive nanowires.…”
Section: Electroless Silver Plating Of Nanoparticle-modified Peptide mentioning
confidence: 99%
See 1 more Smart Citation
“…32 For recombinant amyloid proteins, gold nanoparticles attached to the protein surface serve as nucleation sites to promote the electroless reduction of silver and gold enabling nanowire growth. Only one metal nanoparticle per 250 amino-acids was needed to create conductive nanowires.…”
Section: Electroless Silver Plating Of Nanoparticle-modified Peptide mentioning
confidence: 99%
“…Only one metal nanoparticle per 250 amino-acids was needed to create conductive nanowires. 32 Therefore, we expected treatment of our lysine-substituted peptides with amine-reactive gold nanoparticles, which will attach to amine functionalities at the N-terminus and lysine sidechain groups, followed by self-assembly under analogous conditions to yield nanoparticle decorated fibers suitable for nanowire growth from electroless silver plating. We found that self-assembly was not affected by this gold nanoparticle treatment as micrometer-long fibers could still be observed by TEM (Fig.…”
Section: Electroless Silver Plating Of Nanoparticle-modified Peptide mentioning
confidence: 99%
“…[1][2][3][4][5][6] In parallel to these developments, surfaces and cavities spanned by protein higher-order aggregates have been exploited for molecular encapsulation and for templating nanoparticle synthesis. Typical examples include protein fibrils, [7,8] ferritin, [9,10] S-layers, [11][12][13] antibodies, [14] peptide amphiphiles, [15] capsids, [16][17][18][19] leucine zippers, [20] etc. [21][22][23][24][25][26] Controlled protein aggregation is a critical process in many areas, ranging from biomineralization [27] to neurodegenerative diseases.…”
mentioning
confidence: 99%
“…Furthermore, this nanofiber has potential to act as a template for nanoscale fabrication and core for nanoscale devices [6]. Therefore, it is important to understand the self-assembly process of amyloid.…”
Section: Amyloid Nanofibermentioning
confidence: 99%